2020
DOI: 10.1038/s41405-020-0030-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic evaluation of indirect pulp treatment of young permanent molars using photo-activated oral disinfection versus calcium hydroxide: a randomized controlled pilot trial

Abstract: BACKGROUND: Calcium hydroxide is the most commonly used material in indirect pulp treatment (IPT). However, its drawbacks required its replacement by other materials. AIM: This study aims to estimate clinically and radiographically the success of indirect pulp treatment of young permanent molars with either photo-activated oral disinfection (PAD) or calcium hydroxide. DESIGN: This Randomized Controlled Pilot Trial included 32 vital first permanent molars with deep caries that were treated by indirect pulp trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…who reported that teeth without any clinical/radiographic signs and symptoms were considered as success and IPT showed high survival rates in primary and permanent teeth. [ 24 ] Our results contradict the results by de Assunção Pinheiro IV et al . wherein no change in RDT was observed even after 12 months which could be due to the inability to precisely measure the lesion depth.…”
Section: Discussioncontrasting
confidence: 99%
“…who reported that teeth without any clinical/radiographic signs and symptoms were considered as success and IPT showed high survival rates in primary and permanent teeth. [ 24 ] Our results contradict the results by de Assunção Pinheiro IV et al . wherein no change in RDT was observed even after 12 months which could be due to the inability to precisely measure the lesion depth.…”
Section: Discussioncontrasting
confidence: 99%
“…BDJ Open does, however, publish full clinical trials, and again, the results of these can be accessed by anyone with an internet connection which helps with dissemination of new knowledge. There were eight such papers published in BDJ Open in 2019-2020, 27,28,29,30,31,32,33,34 on topics including experimental dentine hypersensitivity toothpastes 27 and smartphone applications. 30…”
Section: Health Technology Assessment/clinical Interventionsmentioning
confidence: 99%